The Wormhole of Work Engagement: The Empowerment of Personal Resources - I Gusti Ayu Putu Wita Indrayani; I Wayan Gede Supartha; I Gusti Ayu Manuati Dewi; Putu Saroyini Piartrini (Universitas Pendidikan Ganesha, 2023)
A growing body of empirical studies on work engagement has been conducted to investigate the predictors of work engagement from a resource perspective. However, previous research on work engagement has focused solely on the ownership of job resources, dismissing personal resources owned by individuals as distinct entities. The current study evaluates the literature on work engagement, identifies the research gaps, and proposes a research agenda for the future. A systematic literature review of 54 articles from top-tier journals was conducted to achieve the research objective. This study adds to the literature by constructing a conceptual analysis that expands on the theoretical understanding of work engagement. As such, it sheds light on how personal resources play a critical role in increasing work engagement. Personal resources may supplement and reinforce job resources, allowing individuals to articulate the company's vision into more effective business processes. The potential role of self-efficacy as a strong personal resource that can predict and enhance work engagement is one of the most significant findings in this study. Furthermore, the current study emphasizes the need for methodological advances, multilevel analysis, and the expansion of work engagement construction across a wide range of contexts and industries around the world.